2016
DOI: 10.1007/s10198-016-0798-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of poor adult health on labor supply in the Russian Federation

Abstract: We examine the labor supply consequences of poor health in the Russian Federation, a country with exceptionally adverse adult health outcomes. In both baseline OLS models and in models with individual fixed effects, more serious ill-health events, somewhat surprisingly, generally have only weak effects on hours worked. At the same time, their effect on the extensive margin of labor supply is substantial. Moreover, when combining the effects on both the intensive and extensive margins, the effect of illness on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
5
2
1
Order By: Relevance
“…On the one hand, the findings of this study are similar to the studies of Fogel [38] and Jack [35], which found that healthier the labor force is, the higher productivity is, which also means that peasant households with better health tend to experience less CA. On the other hand, the findings of this study are different from the studies of Currie and Madrian [45] and Goryakin and Suhrcke [52], which found that unhealthy people might not stop working, which also means that health status does not affect the quantity of the labor supply. However, labor supply includes not only the quantity of the supply but also the quality of the supply.…”
Section: Discussioncontrasting
confidence: 99%
“…On the one hand, the findings of this study are similar to the studies of Fogel [38] and Jack [35], which found that healthier the labor force is, the higher productivity is, which also means that peasant households with better health tend to experience less CA. On the other hand, the findings of this study are different from the studies of Currie and Madrian [45] and Goryakin and Suhrcke [52], which found that unhealthy people might not stop working, which also means that health status does not affect the quantity of the labor supply. However, labor supply includes not only the quantity of the supply but also the quality of the supply.…”
Section: Discussioncontrasting
confidence: 99%
“…Wraz z obserwowaną w ostatnich latach w wysoko rozwiniętych gospodarkach rynkowych tendencją wzrostu obciążenia zasobów pracy długookresowymi konsekwencjami złego stanu zdrowia coraz większego zaznaczenia na gruncie nauk ekonomicznych zaczyna nabierać aspekt fizyczny kapitału ludzkiego. Zły stan zdrowia stanowi obecnie jedną z głównych przyczyn dezaktywizacji zawodowej zasobów siły roboczej, a problem relacji zachodzących między zdrowiem społeczeństwa a jego produktywnością, zarówno na poziomie pojedynczych przedsiębiorstw, jak i całych gospodarek, stał się przedmiotem coraz liczniejszych badań (Bloom i in., 2004;Goryakin, Suhrcke, 2017). W tym kontekście kluczowego znaczenia nabiera kwestia właściwego pomiaru i wyceny ograniczonej w następstwie złego stanu zdrowia produktywności zasobów ludzkich, zarówno w odniesieniu do oceny możliwości rozwoju całej gospodarki, jak również na poziomie procesu optymalizacji wydajności czynników wytwórczych w przedsiębiorstwie.…”
Section: Ekonomiczny Wymiar Zdrowia Pracowników -Zarys Problemuunclassified
“…Poor health conditions currently constitute one of the main causes of professional deactivation of labour force resources. For this reason, the relations between the health of society and its productivity on the level of both individual companies and whole economies have become the subject of increasing research (WHO, 2001;Bloom et al, 2004;Abegunde & Stanciole, 2006, Goryakin & Suhrcke, 2017. The unfavourable effects on the labour market and the losses connected with these effects in the global production constitute an aggregation of several components.…”
Section: Introductionmentioning
confidence: 99%